2017
DOI: 10.1007/s40534-017-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of lateral vehicular interactions in heterogeneous traffic with weak lane discipline

Abstract: Heterogeneous traffic conditions prevail in developing countries. Vehicles maintain weak lane discipline which increases lateral interactions of vehicles significantly. It is necessary to study these interactions in the form of maintained lateral gaps for modeling this traffic scenario. This paper aims at determining lateral clearances maintained by different vehicle types while moving in a heterogeneous traffic stream during overtaking. These data were collected using an instrumented vehicle which runs as a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The lateral clearance estimated from the developed model is comparable with the results of Minh et al ( 45 ) (that is, 1.416 m versus 1.370 m), and slightly higher than that of Budhkar and Maurya ( 21 ) at 60 km/h speed (that is, 1.669 m versus 1.312 m), but for the remaining cases, the obtained value is lower than that obtained in other studies: Minh et al ( 45 ) for exclusive MTW lane, Chunchu et al ( 22 ) and Budhkar and Maurya ( 21 ) for 30 km/h speed. Conversely, the critical lateral clearance in the current study is found to be higher than the results of Nakatsuji and Nguyen ( 16 ) (that is, 1.447 m versus 0.520 m), but slightly lower than the value reported in Minh et al ( 20 ) (1.145 m versus 1.772 m).…”
Section: Results and Analysissupporting
confidence: 84%
See 3 more Smart Citations
“…The lateral clearance estimated from the developed model is comparable with the results of Minh et al ( 45 ) (that is, 1.416 m versus 1.370 m), and slightly higher than that of Budhkar and Maurya ( 21 ) at 60 km/h speed (that is, 1.669 m versus 1.312 m), but for the remaining cases, the obtained value is lower than that obtained in other studies: Minh et al ( 45 ) for exclusive MTW lane, Chunchu et al ( 22 ) and Budhkar and Maurya ( 21 ) for 30 km/h speed. Conversely, the critical lateral clearance in the current study is found to be higher than the results of Nakatsuji and Nguyen ( 16 ) (that is, 1.447 m versus 0.520 m), but slightly lower than the value reported in Minh et al ( 20 ) (1.145 m versus 1.772 m).…”
Section: Results and Analysissupporting
confidence: 84%
“…Based on the performance measures, it can be observed that the lateral clearance model developed by Minh et al ( 45 ) for undivided carriageway performs reasonably well compared with the linear models developed in the same work ( 45 ) for exclusive motorcycle lane, and with Budhkar and Maurya ( 21 ). Conversely, the critical lateral clearance symbolic model was compared with the dynamic lane width model ( 20 ) and the performance measure for the latter resulted in higher errors.…”
Section: Results and Analysismentioning
confidence: 73%
See 2 more Smart Citations
“…Lateral distance headway is the safe distance between two adjacent parallel vehicles. This can be used to characterize traffic heterogeneity [35]. As the lane width decreases, this headway decreases.…”
Section: Simulations and Numerical Validationmentioning
confidence: 99%